Towards improving hospital workflows: An evaluation of resources to mobilize patients. (16th August 2018) - Pottenger, Brent C.; Pronovost, Peter J.; Kreif, Julie; Klein, Lisa; Hobson, Deborah; Young, Daniel; Hoyer, Erik H.
Abstract : Aim: To characterize resources to safely mobilize different types of hospitalized patients. Background: Current approaches to determine nurse–patient ratios do not always include information regarding the specific demands of patients who require extra resources to mobilize. Workflows must be designed with knowledge of resource requirements to integrate patient mobility into the daily nursing team care plan. Methods: Nurse‐led mobility sessions were evaluated on two adult hospital units, which consisted of nurse–patient encounters focused on patient mobility only. The resources assessed for each session were time‐to‐mobilize patient, time‐to‐document, need for additional staff support, and the need for assistive devices. Mobility sessions were also categorized by patient ambulation status, level of mobility limitations (low, medium and high) and diagnosis. Results: In 212 total mobility sessions, the median time‐to‐mobilize and time‐to‐document were 7.75 and 1.27 min, respectively. Additional staff support was required for 87% and 92% of patients with medium and high mobility limitations, respectively. All patients with low mobility limitations ambulated, and only 14% required additional staff. Ambulating patients with high mobility limitations was the most time‐intensive (median 12.55 min). Ambulating stroke patients required one additional staff and an assistive device in 92% and 69% of the sessions, respectively. Conclusion: This study describes the resources associated with mobilizing inpatients with different levels of mobility impairments and diagnoses. Implications for Nursing Management: These results could assist nursing management with facilitating appropriate daily nurse–patient ratios and justify the need for assistive devices and staff support to safely mobilize patients.